Радиоактивность почв Хубсугул и Баярхонгорского аймака - Далхсүрэн, Б.; Ц. Намчинсүрэн2 (Scientific transaction of the National University of Mongolia. Physics, 2022)
The investigation has been performed at the Nuclear Research Centre National University of Mongolia. A method of determination of man- made and natural radioactivity nuclides in soil samples, using HP-Ge gamma spectrometer is discussed. Results of measurements of radionuclides in soil samples, collected from 2 different regions of Bayanhongor and Huwsgul aimag, were presented. It is determined a specific radioactivity of soil compared with world data.